Efficacy and safety of unilateral axilla-bilateral areola approach for robotic thyroidectomy versus open surgery for thyroid cancer - LIU Haifeng; ZHANG Ye; DU Junze; ZENG Lingjuan; ZHONG Ling (Di-san junyi daxue xuebao, 2022)
Objective To compare the efficacy and safety of unilateral axilla-bilateral areola approach (UABA) for robotic thyroidectomy with conventional open surgery in thyroid cancer patients. Methods We retrospectively analyzed the clinical data of 229 patients who were diagnosed with thyroid cancer and underwent total thyroidectomy plus bilateral central node dissection in the Department of Breast and Thyroid Surgery, First Affiliated Hospital of Army Medical University from January 2018 to May 2020, including 105 cases undergoing robotic surgery (robotic group) and 124 cases undergoing conventional open surgery (open group). All of them were followed up for 12 to 36 months. The hypoparathyroidism, recurrent laryngeal nerve injury, operation time, intraoperative blood loss, drainage volume within postoperative 3 days, postoperative complications and patient satisfaction with neck appearance were recorded and compared between 2 groups. Results The incidences of transient hypoparathyroidism (28.57% vs 64.52%, P=0.000) and permanent hypoparathyroidism (0 vs 5.65%, P=0.016) were significantly lower in the robot group than the open group. So was the rate of permanent recurrent laryngeal nerve injury (0 vs 5.65%, P=0.016). The patients in the robotic group obtained significantly higher satisfaction than those of the open group (100% vs 87.1%, P < 0.001). However, operation time (156.57±37.87 vs 113.98±46.03 min, P < 0.001) was longer, and drainage volume within 3 d postoperatively (141.57±43.16 vs 120.79±49.96 mL, P < 0.001) was statistically larger in the robotic group than the open group. There were no significant differences in intraoperative blood loss (50.31±23.37 vs 50.48±13.67 mL, P=0.455), number of removed lymph nodes (11.23±6.77 vs 12.97±6.77, P=0.055) and postoperative thyroglobulin level (1.01±5.36 vs 1.43±8.47 ng/mL, P=0.330) between the 2 groups. No recurrence or metastasis was observed in the 2 groups during the follow-up period. Conclusion Compared with open surgery, unilateral axilla-bilateral areola approach for robotic surgery shows similar therapeutic effect, but it can better protect the parathyroid gland and recurrent laryngeal nerve and preserve the neck appearance by super-meticulous capsular dissection.